53. PREVALENCE OF MEDICATION ADHERENCE AMONG OUTPATIENTS AT NGHE AN LUNG HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to describe the prevalence of medication adherence among outpatients with chronic obstructive pulmonary disease (COPD) at Nghe An Lung Hospital in 2024.Methods: A cross-sectional study was conducted on 399 outpatients with COPD at Nghe An Lung Hospital in 2024. Medication adherence among study participants was assessed using the Morisky-8 Scale (MMAS-8).Results: Among 399 study participants, the rate of high and low adherence was 55.0% and 12.0%, respectively. The proportion of female participants who sometimes stopped taking the medicine when feeling the symptoms were under control was higher than that of males. There was a significant difference with p-value
Keywords: medication adherence; chronic obstructive pulmonary disease COPD.